Dukungan keluarga dan job crafting pada karyawan wanita yang telah menikah - Kholifah Umi Sholihah; Hidayatillah, Dwi Hasnalathifani; Nabila, Aula Fata (Universitas Muhammadiyah Malang, 2024)
Married women employees will experience difficulties in balancing multiple roles which will have an impact on employee welfare so that employees will have difficulty carrying out job crafting. The aim of this research is to determine the effect of family support on job crafting among married women employees. This research is quantitative research. Sampling used convenience sampling involving 51 married working women. Data analysis used simple linear regression with SPSS 25. This research found that family support had a positive correlation with job crafting as indicated by a significant value of 0,012. The effective contribution given by family support to job crafting is 12,3%. Based on this research, to improve job crafting, the government or academics can provide education on the importance of family support for a working woman.